2022
DOI: 10.21037/apm-22-1344
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic change in the thickness of the masseter muscle between contraction and relaxation is associated with the masticatory function in older adults: a cross-sectional study

Abstract: Background: Decreased masticatory function contributes to malnutrition in the elderly. The purpose of our study was to explore whether the masseter muscle is involved in masticatory function in older adults and to help determine if the masticatory function of the elderly can be improved by exercising the masseter muscle.Methods: Random sampling was adopted in our research, and a total of 413 older adults from 9 nursing homes in China were recruited from March 10 to June 12, 2022. The thickness and echo intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
10
2
Order By: Relevance
“…Furthermore, hypotrophy and atrophy can affect facial muscles, including masseter muscle, which has functional and aesthetic consequences. 10 Different techniques have been described to address a weak or poorly defined jawline, but to our knowledge, none of them have used our approach, which directly enhances masseter muscle volume. This particular location is critical to address as vital structures pass through it, and improper technique can result in serious injuries to the passing structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, hypotrophy and atrophy can affect facial muscles, including masseter muscle, which has functional and aesthetic consequences. 10 Different techniques have been described to address a weak or poorly defined jawline, but to our knowledge, none of them have used our approach, which directly enhances masseter muscle volume. This particular location is critical to address as vital structures pass through it, and improper technique can result in serious injuries to the passing structures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hypotrophy and atrophy can affect facial muscles, including masseter muscle, which has functional and aesthetic consequences. 10…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, frailty is associated with sarcopenia, of which one of the indicators is calf circumference (CC) 6 7. It has been reported that chewing8 9 and swallowing10 11 functional decline are associated with decreased CC. A cross-sectional study conducted on older adults has revealed that poor chewing function is significantly related to gastrocnemius muscle thickness, which is a component of the calf 8.…”
Section: Introductionmentioning
confidence: 99%